The Effect of Bases, Catalyst Loading and Reaction Temperature on the Catalytic Evaluation of Supported Palladium(II) Catalyst in the Mizoroki-Heck - Kamilah Che Soh, Siti; Aminah Jusoh, Siti; Sukeri Mohd Yusof, Mohd; M. Khairul, Wan; Shamsuddin, Mustaffa (International Journal of Engineering and Technology, 2018)
The coupling reaction between aryl halide of 4-bromoacetophenone with methyl acrylate in the presence of supported palladium(II) catalyst has been investigated. The synthesized catalyst is air and moisture-stable turned out to be efficient and selective for Mizoroki-Heck reaction under operating conditions. Three parameters have been explored to monitor the performance of catalytic activities whichÂ Â Â focused on the effect of bases, catalyst loading and reaction temperature. Furthermore, the catalyst can be easily recovered quantitatively by simple filtration and reused in at least three consecutive cycles of Mizoroki-Heck reaction.Â Â